Description of the male of Darditilla araxa (Cresson, 1902) (Hymenoptera, Mutillidae) with geographical distribution, biological notes and key to males of Brazil - Lopez, Vinicius M.; Guillermo-Ferreira, Rhainer; Trad, Bhrenno M.; Silvestre, Rogerio (Zootaxa, 2018)
The previously unknown male of Darditilla araxa is here described based on association with females in copula. We also present a map with its geographical distribution, additional biological notes and a key for known Brazilian males of Darditilla.